Optimalisasi Fungsi BUMdes Melalui Penguatan Manajemen dalam Mengembangkan Potensi Ekonomi Desa Wisata Ngargogondo Borobudur - Lucia Rita Indrawati; Ghina Fitri Ariesta Susilo; Suci Nasehati Sunaningsih; Alkadri Kusalendra Siharis; Chaidir Iswanaji (Solidaritas: Jurnal Pengabdian, 2021)
Ngargogondo Village is one of the tourist villages located in the Menoreh Mountains range 3 kilometers southeast of the Borobudur Temple Tourism Object. Based on its geographical location, Ngargogondo Village has the potential as a tourist village that can improve the residents' economy. Based on the results of initial observations in the Ngargogondo Village area, the biggest problem faced is the lack of synergy between the village government, village communities, business actors, and BUMDes in order to develop the village's economic potential. This is due to the lack of awareness and motivation of BUMDes managers, Weak management of BUMDes management, BUMDes business activities are not innovative and tend to be passive. develop village potential. PKM activities are carried out in Ngargogondo village using various implementation methods, including observation, lectures and discussions, direct practice, supervision and evaluation. how to design a good Business Plan, including how to calculate the cost of production and efficient production in generating profits for BUMDes. recommendations for further PKM activities can be held seminars and training on promotional techniques so that the BUMDes of Ngargogondo Village can develop rapidly